ASSESSMENT OF DRINKING WATER QUALITY OF A COASTAL VILLAGE OF KARACHI (Biological Sciences - PJSIR, 2004)
The drinking water quality of a coastal community in Rehri village, Karachi was assessed for human consumption by studying the chemical and microbiological parameters to determine the suitability of domestic drinking water usage. Water samples were collected at household levels from storage tanks and storage containers (earthen jars), main supply line and springs present in the vicinity. Samples collected from different sources indicated that bacterial counts were high for the storage tanks than the earthen jar containers. In storage tanks 71% samples were in high to very high health risk category whereas, in earthen jars 50% samples were in low health risk category. Water samples from two springs showed that samples of Chashma spring had high bacterial count (336 MPN index/100 ml) coupled with high concentration of NO3 (29.681 mg/l) as compared to Rehri spring (41 MPN index/100 ml, 8.417 mg/l, bacterial count and nitrate concentra- tions, respectively). All samples collected at household level showed that bacterial contamination exceeded the maxi- mum acceptable concentration. Other parameters (NO3, NO2, NH3 PO4, free Cl, Ca and Mg hardness) studied including trace elements (Fe, Cu, Cr) in the drinking water were below the WHO drinking water quality guidelines. Fecal coliform, Escherichia coli was also detected including important pathogens Serratia sp. and Enterobacter sp. which were isolated and indicated possible fecal contamination of drinking water at all levels.